Altered corticostriatal functional connectivity in individuals with high social anhedonia. Issue 1 (28th August 2015) - Wang, Y.; Liu, W.-H.; Li, Z.; Wei, X.-H.; Jiang, X.-Q.; Geng, F.-L.; Zou, L.-Q.; Lui, S. S. Y.; Cheung, E. F. C.; Pantelis, C.; Chan, R. C. K.
Abstract : Background: Dysregulation of the striatum and altered corticostriatal connectivity have been associated with psychotic disorders. Social anhedonia has been identified as a predictor for the development of schizophrenia spectrum disorders. The aim of the present study was to examine corticostriatal functional connectivity in individuals with high social anhedonia. Method: Twenty-one participants with high social anhedonia score and 30 with low social anhedonia score measured by the Chinese version of the Revised Social Anhedonia Scale were recruited from university undergraduates (age 17–21 years) to undergo resting-state functional MRI scans. Six subdivisions of the striatum in each hemisphere were defined as seeds. Voxel-wise functional connectivity analyses were conducted between each seed and the whole brain voxels, followed by repeated-measures ANOVA for the group effect. Results: Participants with high social anhedonia showed hyper-connectivity between the ventral striatum and the anterior cingulate cortex and the insula, and between the dorsal striatum and the motor cortex. Hypo-connectivity in participants with high social anhedonia was also observed between the ventral striatum and the posterior cingulate cortex. Partial correlation analyses further showed that the functional connectivity between the ventral striatum and the prefrontal cortex was associated with pleasure experience and emotional suppression. Conclusions: Our findings suggest that altered corticostriatal connectivity can be found in participants with high levels of social anhedonia. Since social anhedonia has been considered a predictor for schizophrenia spectrum disorders, our results may provide novel evidence on the early changes in brain functional connectivity in at-risk individuals.